INDONESIAN CENTER FOR AGRICULTURAL LIBRARY AND TECHNOLOGY DISSEMINATION, BOGOR, INDONESIA - Winarko, Bambang (Malaysian Journal of Library and Information Science, 2017)
Pesantrens are traditional Islamic boarding schools in Indonesia. Pesantrens play significant roles in education, particularly Islamic teaching synergy with the secular education systems. However, Pesantrens these days are facing an environment that could be detrimental to their existence as a traditional education system. This challenge comes from the Internet technology penetration in Indonesia, which brings about changes in almost all aspects of living. This paper describes the application of Internet technology in Islamic teaching and the role of Internet technology on Pesantren online. The study was conducted by searching the available Pesantrens online using search engines, and investigated the content to reveal the applied Internet technology, benefit of Internet technology for Pesantrens, content of the Pesantrens’ web sites, and a comparison between the previous and present investigation of Pesantrens online. The study found that information about the 46 pesantrens online were available in the Internet and uses 16 Internet technology applications. It also showed that Pesantrens had diverse roles such as informational, advertising and teaching purposes. The study revealed that the development of the pesantren online includes increasing the number of Internet technology application as well as the number of pesantren online.